USE OF LAB-GROWN ORGANOIDS IN DISEASE MODELING - Ali Yahya Mater , Mohammed Ali Majari , Mohammed Ali Mohammed Anbari , Hassan Mohammed Ghabesh Ayashi , Afnan Mohammed Kulip Ali , Abdulqader Ali Ahmed Muthaffar ,Yahia Othman Ahmed Ghaish , Mohammed Awadh Almutairi , ,; Walaa Abdulwahed Khalid , Nouf Abdulqader Hassan , Mohammed Amer Asiri , Jameel Abdulrahman Alnemari , Fayez Saleem Aldhaferi , Maha Mohammed Moteq Almotairi , Fawaz Awad Zaben Alenazi, (Chelonian Research Foundation, 2022)
Ensuring accurate and dependable test findings is of utmost importance in clinical labs, making quality improvement essential. Given the growing recognition of the possible negative impact of mistakes in laboratory procedures on patient results, it is crucial to underline the ongoing need for enhancing laboratory services. A systematic literature review was performed on PubMed and the Web of Science Core Collection from October to February 2021 to assess the scientific rigor of medical laboratory quality enhancement studies. Only peer-reviewed articles published in English that satisfied the criteria for quality improvement were considered. Data extraction was performed using a standardized template, and the publications were evaluated using the Quality Improvement Minimum Quality Criteria Set (QI-MQCS) on a scale ranging from 0 to 16. Of the total 776 papers, 726 were assessed for the examination of quality in clinical laboratory literature. The studies were examined based on quality enhancement and monitoring methodologies and interventions, including education, training, task power, and monitoring. The findings revealed that the average rating of QI-MQCS for quality development articles published between 1981 and 2000 was 2.5. In contrast, for papers published between 2001 and 2020, the mean score was 6.8. This suggests a consistent and significant enhancement in quality within the clinical laboratory field. Nevertheless, there is an opportunity to develop a comprehensive framework for evaluating the quality of medical laboratory research and enhancing accreditation initiatives in the field. Keywords: performance assessment, laboratory quality, comprehensive quality management, QI-MQCS